Decomposing Productivity Growth in Chinese Manufacturing - Wang, Bin; Zhang, Guangnan; Peoples, James (Asian Journal of Empirical Research, 2017)
In an increasingly globalized business environment, sustaining relatively high productivity growth is essential for maintaining an international competitive advantage. Economists typically identify manufacturing companies in China as prime examples of firms attaining cost competitiveness through productivity growth. This study contributes to the analysis of productivity growth in China by estimating unexplained technological change, scale and infrastructure investment’s contribution to annual productivity growth for 27 manufacturing industries. A flexible form cost equation for manufacturing industries classified at the two-digit industry code level for the 1998-2005 sample period is used to investigate each factor’s impact on productivity growth. The findings suggest that for all industries excluding furniture manufacturing, unexplained technological change contributes to productivity growth. Infrastructure investment and scale contribute to such growth for 16 and 5 of the 27 industries respectively.